Acute Toxicity and Neurotoxicity of Chlorpyrifos in Black Tiger Shrimp, Penaeus monodon - Tassanee Eamkamon (EnvironmentAsia, 2012)
Acute toxicity and neurotoxicity of chlorpyrifos were determined in black tiger shrimp, P. monodon. LC50 values after 24 to 96 h of exposure were between 149.55 and 59.16 nmol/L. To determine the neurotoxicity of chlorpyrifos, the inhibition of acetylcholinesterase was monitored in the gill of the shrimps exposed to lethal (0.019, 0.194, and 1.942 µmol/L) and sub-lethal (0.019, 0.194, and 1.942 nmol/L) concentrations of chlorpyrifos. In lethal dose exposure, the AChE activities observed in shrimp exposed to 0.194, and 1.942 µmol/L of chlorpyrifos were significantly lower (1.7 and 3.3 times) than that of control shrimp after 30 min of exposure (p<0.05). In sub-lethal exposure tests, the AChE activity of shrimp was significantly lower (1.9 times) than that of control shrimp after exposure to 1.942 nmol/L of chlorpyrifos for 72 h (p<0.05). The sensitive reduction of AChE activity at the sub-lethal concentration, which was 30 times lower than 96 h LC50 value found in this study, indicates the potential use as a biomarker of chlorpyrifos exposure.